READOUT ALGORITHM FROM A FOCUSED MICRORESISTIVITY LOGS - KURHANSKYI, V.; TISHAIEV, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In article rate a possibility to development readout algorithm from a focused microresistivity logs on basis of discrete wavelet transform.